Interferon Lambda in the Pathogenesis of Inflammatory Bowel Diseases - Wallace, Jonathan W.; Constant, David A.; Nice, Timothy J. (Frontiers in Immunology, 2021)
Interferon λ (IFN-λ) is critical for host viral defense at mucosal surfaces and stimulates immunomodulatory signals, acting on epithelial cells and few other cell types due to restricted IFN-λ receptor expression. Epithelial cells of the intestine play a critical role in the pathogenesis of Inflammatory Bowel Disease (IBD), and the related type II interferons (IFN-γ) have been extensively studied in the context of IBD. However, a role for IFN-λ in IBD onset and progression remains unclear. Recent investigations of IFN-λ in IBD are beginning to uncover complex and sometimes opposing actions, including pro-healing roles in colonic epithelial tissues and potentiation of epithelial cell death in the small intestine. Additionally, IFN-λ has been shown to act through non-epithelial cell types, such as neutrophils, to protect against excessive inflammation. In most cases IFN-λ demonstrates an ability to coordinate the host antiviral response without inducing collateral hyperinflammation, suggesting that IFN-λ signaling pathways could be a therapeutic target in IBD. This mini review discusses existing data on the role of IFN-λ in the pathogenesis of inflammatory bowel disease, current gaps in the research, and therapeutic potential of modulating the IFN-λ-stimulated response.